A study of HYDROPOL2D and SWAT+GWFLOW models to improve flood forecasting: a case study in Brazil - De Angelis, Cristiano Trindade (Brazilian Journal of Production Engineering, 2026)
Limited studies have assessed the effects of land management practices on hydrologic processes and agronomic responses in fully integrated stream-aquifer systems, considering the whole picture: hydrology - agroforestry systems - humans - biodiversity. As climate change intensifies and urban vegetation is increasingly altered, urban basins are experiencing more frequent and severe flood events. Hydrodynamic models are vital for understanding and managing these events, but they often rely on hydrometric station data that can be both scarce and inaccurate, especially during extreme weather. This research focuses on how combining structural strategies with non-structural approaches can improve flood resilience and emergency response planning. The central research question asks: How does culture influence flood management systems (including hydrodynamic modeling) and drainage-related challenges like waterlogging? A key outcome of the study is the identification of a Knowledge Management and Social Participation framework as a useful tool for creating an effective flood management plan using the HydroPol2D model. However, the limitations of HydroPol2D, particularly its lack of consideration for agricultural impacts on hydrology, lead to the recommendation of using the SWAT+ model alongside the GWFlow groundwater module to provide a more integrated and robust hydrological evaluation.
Keywords: knowledge management; bio-dynamic model; Culture; hydrodynamic model; organizational intelligence